The Effectiveness of Guided Inquiry Learning Model on Student Learning Outcomes - Fausy, Andi Irvan; Ismail, Ismail; Muis, Abd. (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2023)
This study aimed to determine the learning outcomes of students who were taught using the guided inquiry learning model and to determine the effectiveness of the implementation of the trained inquiry learning model on the learning outcomes. This research was a pre-experimental research using one group pretest-posttest design. The population in this study were students of class X science. The sample of this study was selected with a specific purpose (purposive sampling), namely the technique of determining the model with specific considerations so that one class was obtained, which amounted to 23 students. The data collection technique was through multiple-choice test before (pretest) and after (posttest). The analysis technique used is descriptive analysis and the N-Gain test. The results showed that student learning outcomes using the guided inquiry learning model increased before and after treatment, from 60.00% to 84.00%. Based on the N-Gain test, student learning outcomes are in the medium category (59.32%). This shows that learning using the guided inquiry learning model in biology learning is effective in improving the learning outcomes.